2021
DOI: 10.18203/2394-6040.ijcmph20213524
|View full text |Cite
|
Sign up to set email alerts
|

Identification of risk factors for road traffic accidents using injured drivers: a cross sectional study conducted in Sri-Lanka

Abstract: Background: Road traffic accidents are a significant cause of morbidity and mortality worldwide and a major cause of sudden deaths in Sri Lanka.Methods: This study was conducted to assess risk factors for RTAs using 360 injured drivers, admitted to the accident wards in two teaching hospitals in Kandy and Kurunegala using interviewer-administered questionnaires.Results: The majority of the study population (97%) was male and most drivers were 26-35 years of age. Motorcycles were the most common vehicle (79%) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
(21 reference statements)
1
0
0
Order By: Relevance
“…This research established a connection between the type of vehicle and RTAs. Consistent with this study, vehicle type was associated with RTAs in the Philippines [ 30 ], Iraq [ 31 ], and Sri Lanka [ 32 ]. This association may be due to the fact that drivers of vehicles such as Vitz, buses, and water trucks often drive at high speeds without exercising adequate caution.…”
Section: Discussionsupporting
confidence: 82%
“…This research established a connection between the type of vehicle and RTAs. Consistent with this study, vehicle type was associated with RTAs in the Philippines [ 30 ], Iraq [ 31 ], and Sri Lanka [ 32 ]. This association may be due to the fact that drivers of vehicles such as Vitz, buses, and water trucks often drive at high speeds without exercising adequate caution.…”
Section: Discussionsupporting
confidence: 82%
“…This is also in line with a finding from Benin City, Nigeria, which found less experienced drivers inflicting more RTC than experienced drivers (Okafor et al, 2017). Findings from research conducted in countries of all development levels indicated a relationship between a lack of sufficient driving experience and risky driving behaviours (Mekonnen et al, 2016;Liu et al, 2021;Madhumali et al, 2021). The occurrence of risky driving behaviours is associated with a greater likelihood of the occurrence of RTC (WHO, 2018).…”
Section: Discussionsupporting
confidence: 79%
“…Furthermore, our research revealed that limb injuries were the most commenest types of injuries, accounting for 42.2% in lower and 27.5% in upper limb respectively. In a separate study conducted in Sri Lanka, head injuries were the primary concern [9], while other studies showed a high incidence of leg (39.7%) and limb injuries (73%) [8], as well as head and limb injuries (70% & 73%) [12].…”
Section: Discussionmentioning
confidence: 91%
“…In 2013, the majority of victims fell within the age range of 19 to 39 years [7], and in 2021, it was the 26 to 35 age group that was most affected [8]. In 2022, victims ranged from 1 to 75 years of age [10], but the age group of 18 to 45 years is typically considered the most active and productive.…”
Section: Discussionmentioning
confidence: 99%